2020
DOI: 10.15218/zjms.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin K on the wound healing process in rat skin achieved by common wound dressing agents

Abstract: Six groups of albino rats were used (6 rats in each group). Group M received Mebo ointment, Group Creceived Cica silver spray, Group K received Vitamin K injection, Group MK received Mebo ointment+vitamin K injection.Group CK received Cica silver spray +vitamin K Group, and Group N received no-treatment. The duration of the experiments was as 7, 14, and 21 days post wound surgery.The percentage of wound contraction was measured, and the blood serum was collected to test the level of transforming growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The areas near the closure of wounds were detected at days 0, 5, 10, and 15 after excision. The percentage of wound closure was determined by utilizing a transparency paper and a marker after a partial rat anesthetization by an anesthesia injections containing 0.02 ml of xylazine (3 mg/kg) and 0.18 ml of ketamine (300 mg/kg) [ 33 ]. The graph paper (1 mm 2 ) was relied on to find the wound size, and the transparent paper was important to trace the wound area and area of epithelized tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The areas near the closure of wounds were detected at days 0, 5, 10, and 15 after excision. The percentage of wound closure was determined by utilizing a transparency paper and a marker after a partial rat anesthetization by an anesthesia injections containing 0.02 ml of xylazine (3 mg/kg) and 0.18 ml of ketamine (300 mg/kg) [ 33 ]. The graph paper (1 mm 2 ) was relied on to find the wound size, and the transparent paper was important to trace the wound area and area of epithelized tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The closure area of wounds was determined at different periods (at 0, 5, 10, and 15 days after excision). The wound closure percentage and epithelialized areas were estimated by using a marker, transparency, paper squares, and graph paper (1 mm 2 ) paper after delivery of partial anesthesia (0.1 mL/20 g) through intraperitoneal injections 33 . The closure percentage calculated as follows: normalClosure%=[(WAonday0WAonspecificdayX)/(WAonday0)]×100$$\begin{eqnarray*}{\mathrm Closure} \;\% &=& [(WA\;on\;day\;0 - WA\;on\;specific\;day\;X)/(WA\;on\;day\;0)]\\ && \times \, 100\end{eqnarray*}$$…”
Section: Methodsmentioning
confidence: 99%
“…The wound closure percentage and epithelialized areas were estimated by using a marker, transparency, paper squares, and graph paper (1 mm 2 ) paper after delivery of partial anesthesia (0.1 mL/20 g) through intraperitoneal injections. 33 The closure percentage calculated as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Vitamin K can also inhibit the expression of IL-1β and IL-18 by inhibiting the assembly and activation of NLRP3 inflammasome, which plays a role in inhibiting inflammatory response (Huang et al, 2020;Zheng et al, 2021). The research of Osman et al Frontiers in Pharmacology frontiersin.org (Osman and Amin, 2020) showed that the combination of vitamin K and Mebootment may promote wound healing by promoting the expression of transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF). The results of the corneal epithelial injury mouse model test of Rush et al (2016) show that vitamin K3 can promote corneal epithelial wound healing in vivo.…”
Section: Figurementioning
confidence: 99%